The development of iv grade thematic teaching materials based on local culture of east sumba - Fembriani; Wonda, Hiwa; Taneo , Silvester; Bulu, Vera (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This research was conducted based on the situation in the Social Studies (IPS) learning process which was not effective and efficient because problems were often encountered, that is verbalism in learning because teachers interpreted teaching materials as mere tools and availability of teaching materials was not relevant to the material being taught. This study aims to develop teaching materials based on the local culture of East Sumba that are relevant to Social Studies material in class IV that are valid, practical, and effective. This type of research used development research with the ADDIE Model, which consists of 5 stages, that are Analysis, Design, Development, Implementation, and Evaluation. Collecting research data using questionnaires and tests. The research subjects for class IV SDK Santo Yosep 2 were 25 people. Data collected consisted of expert validation data, teacher and student response questionnaire data, as well as test result data. The results showed that development of teaching materials for IPS class IV SDK Santo Yosep 2 had very good qualifications with an achievement level of 90.41%. The achievement of this quality is obtained from the calculation of average media validity level of 90.83% with very valid qualifications, the practicality level of media is 96.40% with very practical qualifications, and the effectiveness level of media is 84% ​​with very high/effective qualifications. So it can be concluded that diorama media developed is valid, practical, and effective.